Scientific production in sports science journals: Bibliometric analysis Produção científica nos periódicos das ciências do esporte: Análise bibliométrica Producción científica en los periódicos de ciencias del deporte: Análisis bibliométrico - Coimbra D.R.* (2019)
© 2019, Redprint Editora Ltda. All right reserved.The aim of this study was to analyze the scientific production of journals on sport and exercise science and physical education in Portuguese that are indexed in the Scopus database by conducting a bibliometric analysis. Six journals related to this field of study and indexed in the Scopus database were selected. Regarding publications, the journals published 3,869 documents while indexed in Scopus, most (90.8%) of which were original articles. The year with the highest number of publications was 2013 (n = 473). The clusters of keywords that were cited most often (“physical activity” and “exercise”) were related to biodynamics. Most journal authors are from Brazil (89.86%). The Brazilian Journal of Sports Medicine had the highest number of publications (n = 1179), the highest average per year (n = 78.6), and reached the highest index in the scientific journal ranking (SJR index = 0.331). We concluded that scientific production increased until 2013. The publications with the highest number of citations and the most common study topics are related to the area of biodynamics. Level of evidence II; Review Study.